A composite current collector base film and preparation method thereof

By introducing graphene oxide-nano-metal oxide composite materials into the composite fluid collector base film, the problem of insufficient binding force during magnetron sputtering in the traditional base film is solved, and mechanical properties and electrical conductivity are improved.

CN118645633BActive Publication Date: 2025-04-08HUNAN ENERGY FRONTIERS NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410668005.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-04-08
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

The traditional composite fluid-collection base film is prone to problems such as substrate perforation and metal layer falling off during magnetron sputtering, resulting in insufficient binding force.

Method used

Graphene oxide-nano-metal oxide composite material is used as a modifier. By introducing the composite material into the base film, the mechanical properties and surface roughness of the base film are improved and the conductivity is increased.

Benefits of technology

It effectively reduces the perforation phenomenon of the base film during sputtering, improves the bonding force between the base film and metal, and improves the conductivity of the composite fluid collection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118645633B_ABST
    Figure CN118645633B_ABST
Patent Text Reader

Abstract

The present application provides a composite current collector base film, comprising at least polyolefin and a modifier, wherein the modifier comprises a graphene oxide-nanometal oxide composite material. The present invention synthesizes the modifier graphene oxide-nanometal oxide composite material by a hydrothermal method, and introduces the composite material into the base film by virtue of the advantages of the composite material having a high specific surface area, large mechanical properties, and good electrical conductivity, so as to improve the overall mechanical and electrical properties of the base film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery materials, and in particular to the synthesis and preparation method of a negative electrode composite current collector base film used in lithium-ion batteries. Background Art

[0002] The current collector is an important component of lithium-ion batteries. It can collect and output the current generated by the active material and input the electric current to the active material. With the development of lithium battery technology, the thickness, weight and safety of traditional current collectors have gradually failed to meet the needs of high energy density and high safety. In this context, a composite current collector with a "sandwich" structure (metal-base film (insulating layer)-metal) has emerged, in which the insulating layer is generally polymer PP, PET, PI. Compared with traditional aluminum foil or copper foil, the composite current collector is thinner, the metal content is reduced, and because of the presence of an intermediate insulating layer, the thermal runaway of the battery can be effectively reduced when the battery is short-circuited. Such a composite current collector with high energy density, low cost and high safety is expected to be widely used in lithium-ion batteries in the future. At present, the composite copper foil produced in industrial mass production uses PP as the substrate. First, magnetron sputtering is used to produce a 50nm-100nm metal copper layer on both sides of a substrate with a thickness of 4μm-6μm, and then the copper layer is thickened to 1μm-3μm by water electroplating. Compared with traditional pure copper foil, the amount of copper used can be reduced by more than half, significantly reducing production costs.

[0003] Although the composite current collector has better performance than the traditional current collector, there are still many technical difficulties in the large-scale mass production process, such as: 1. During the magnetron sputtering process, metal ions may pierce the substrate when deposited at high speed and high temperature; 2. The bonding force between the substrate and the metal layer is insufficient, causing the metal layer to fall off easily. The reasons for these problems are, on the one hand, due to the insufficient mechanical properties of the polymer itself, which makes it easy to be perforated by metal ions; on the other hand, because the substrate itself is an insulating material and has a smooth surface, the bonding force with the metal is weak, causing the problem of the metal layer falling off easily. Therefore, how to improve the bonding force between the metal layer and the substrate is a key problem that needs to be solved. Summary of the invention

[0004] Therefore, the main purpose of the present application is to provide a composite current collector base film and a preparation method thereof to further optimize the above-mentioned problems.

[0005] In order to solve the above technical problems, the purpose of the present application is to provide a composite current collector base film, which comprises at least: polyolefin and a modifier, wherein the modifier comprises a graphene oxide-nanometal oxide composite material, the nanometal oxide comprises one or more of ZrO2 and TiO2, and the nanometal oxide is attached to the graphene oxide.

[0006] As mentioned above, the composite current collector base film further includes: a toughening agent, a nucleating agent and an antioxidant.

[0007] As described above, the toughening agent includes one or more of polymethyl methacrylate, polybutyl methacrylate, polybutyl acrylate, polyacrylate, polymethyl acrylate, and polystyrene-methacrylate copolymer; the nucleating agent includes a carboxylate nucleating agent, wherein the carboxylate nucleating agent includes one or more of zinc adipate (ZnAA), zinc pimelate (ZnPA), and zinc suberate (ZnSA); the antioxidant includes a hindered phenol antioxidant, wherein the hindered phenol antioxidant includes BHT 264.

[0008] As described above, based on the total weight of the composite current collector base film, the weight proportion of the polyolefin is 70wt%-90wt%, the sum of the weight proportions of the toughening agent, nucleating agent and antioxidant is 0wt%-10wt%, and the weight proportion of the modifier is 10wt%-20wt%.

[0009] As mentioned above, the polyolefin includes polypropylene, wherein the polyolefin is polypropylene with a molecular weight of 200,000-500,000.

[0010] Another object of the present application is to provide a method for preparing the composite current collector base film as described above, comprising the following steps: a melt granulation step: melt granulating the polyolefin and the modifier to form a mixture; and a co-extrusion molding step: melt-extrude the mixture, cool and shape it to form a cast sheet, and then stretch and heat-shape the cast sheet to obtain the composite current collector base film.

[0011] As described above, the preparation method of the modifier includes the following steps: a step of forming a zirconium oxychloride aqueous solution: taking zirconium oxychloride octahydrate and adding it to pure water for ultrasonic dispersion to obtain a zirconium oxychloride aqueous solution; a step of adding and stirring: taking graphene oxide (GO) and adding it to the zirconium oxychloride aqueous solution and stirring it; a pH value adjustment step: adding a certain amount of pH value adjuster to adjust the pH value of the zirconium oxychloride aqueous solution to 10-11 to obtain a mixed solution; and a high temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor, reacting at a high temperature of 150°C-200°C for 12h-24h, then taking out the mixed solution, washing, filtering, and drying to obtain a graphene oxide-nano ZrO2 composite material.

[0012] As described above, the preparation method of the modifier includes the following steps: an intermediate solution forming step: adding tetrabutyl titanate to a mixed solution formed by deionized water and tetrabutylammonium hydroxide to obtain an intermediate solution; adding stirring step: adding graphene oxide to the intermediate solution and stirring it; pH value adjusting step: adding a certain amount of pH value adjusting agent to adjust the pH value of the intermediate solution to 10-11 to obtain a mixed solution; and a high temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor, reacting at a high temperature of 150°C-200°C for 12h-24h, then taking out the mixed solution, washing, filtering, and drying to obtain a graphene oxide-nano-TiO2 composite material.

[0013] As described above, in the melt granulation step, the screw temperature of the granulator is 180°C-230°C, the melt temperature is 200°C-250°C, the pelletizing temperature is 250°C-300°C, and the pelletizing speed is 2000rpm-3000rpm.

[0014] As mentioned above, the pH adjuster includes one or more of potassium hydroxide, ammonia water, sodium hydroxide, sodium dihydrogen phosphate, and potassium dihydrogen phosphate.

[0015] The present application introduces a graphene oxide (GO)-nanometal oxide composite during the production process of the base film, and improves the mechanical properties and surface roughness of the base film by taking advantage of the small particle size, large specific surface area and good mechanical properties of the nanomaterial, thereby reducing the perforation phenomenon of the base film during the sputtering process and improving the bonding force between the base film and the metal to a certain extent; at the same time, a certain amount of graphene oxide is introduced to improve the conductivity of the base film, and the good conductivity of graphene can improve the conductivity of the composite current collector to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the structure of the modifier of this application.

[0017] Figure 2 A schematic block diagram of a process for preparing a composite current collector base film according to an embodiment of the present application.

[0018] Figure 3 A schematic block diagram of a process for preparing a modifier in a composite current collector base film according to another embodiment of the present application.

[0019] Figure 4 A schematic block diagram of a process for preparing a modifier in a composite current collector base film according to another embodiment of the present application.

[0020] Figure 5 A bar diagram showing the ionic conductivity data of a composite current collector-based membrane according to another embodiment of the present application. DETAILED DESCRIPTION

[0021] In order to further explain the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the following, in combination with the accompanying drawings and specific embodiments, describes in detail a composite current collector base film and its preparation method proposed in the present application, its specific implementation method, structure, characteristics and effects.

[0022] The composite current collector base film of one embodiment of the present application comprises: polyolefin, toughening agent, nucleating agent, antioxidant and modifier, wherein the modifier comprises graphene oxide-nanometallic oxide composite material. In some embodiments, the toughening agent comprises one or more of polymethyl methacrylate, polybutyl methacrylate, polybutyl acrylate, polyacrylate, polymethyl acrylate, polystyrene-methacrylate copolymer. The nucleating agent comprises a carboxylate nucleating agent, wherein the carboxylate nucleating agent comprises one or more of zinc adipate (ZnAA), zinc pimelate (ZnPA), zinc suberate (ZnSA), and the antioxidant comprises a hindered phenol antioxidant or BHT 264. The polyolefin comprises polypropylene, wherein the polyolefin is a polypropylene with a molecular weight of 200,000-500,000. In some embodiments, the metal oxide comprises one or more of ZrO2, TiO2, wherein the weight percentage of the polyolefin is 70wt%-90wt%, the weight percentage of the toughening agent, nucleating agent and antioxidant is 0wt%-10wt%, and the weight percentage of the modifier is 10wt%-20wt%. Please refer to Figure 1 , the nano metal oxide is attached to the graphene oxide. In some embodiments, the nano metal oxide is physically attached to the graphene oxide to form a composite material.

[0023] See also Figure 2 In another embodiment, the present application provides a method for preparing a composite current collector base film, which includes the following steps: a melt granulation step: melt granulating the polyolefin, the toughening agent, the nucleating agent, the antioxidant and the modifier to form a mixture; and a co-extrusion molding step: melt-extrude the mixture, cool and shape it to form a cast sheet, and then stretch and heat-shape the cast sheet to obtain the composite current collector base film.

[0024] In this embodiment, the polyolefin in the composite current collector base film is polypropylene, so the toughening agent can increase the toughness and strength of the polypropylene film by adding other polymers. The nucleating agent is to allow polypropylene to form β crystals, which can be biaxially stretched and increase the strength of the polypropylene film TD. As for the antioxidant, it is to prevent oxidation during the melting process of polypropylene. Although toughening agents, nucleating agents and antioxidants may have a certain strength-promoting effect, their effects are very limited and are not necessary formulation components, so they can be chosen not to be added to the composite current collector base film. In other words, the necessary components of the composite current collector base film of the present invention are polyolefins and modifiers, wherein polyolefins are the main structural components of the base film. With the advantages of the high specific surface area, large mechanical properties and good conductivity of the modifier, the modifier is introduced into the base film to improve the overall mechanics, bonding and electrical properties of the base film.

[0025] In this embodiment, the weight proportion of the polyolefin in the melt granulation step is 70wt%-80wt%, the weight proportion of the toughening agent is 5wt%-10wt%, the weight proportion of the nucleating agent is 0wt%-5wt%, the weight proportion of the antioxidant is 0wt%-1wt%, and the weight proportion of the modifier is 10wt%-20wt%. In some embodiments, based on the total weight of the composite current collector base film, the weight proportion of the polyolefin is 70wt%-90wt%, the weight proportion of the toughening agent is 0wt%-10wt%, the weight proportion of the nucleating agent is 0wt%-5wt%, the weight proportion of the antioxidant is 0wt%-1wt%, and the weight proportion of the modifier is 10wt%-20wt%. In some other embodiments, the weight proportion of the polyolefin is 70wt%-80wt%, the weight proportion of the toughening agent is 8wt%-10wt%, the weight proportion of the nucleating agent is 1wt%-3wt%, the weight proportion of the antioxidant is 0wt%-1wt%, and the weight proportion of the modifier is 10wt%-20wt%. Basically, the principle of the weight proportion design of the components is that the weight proportion of the polyolefin is the largest, accounting for at least half, followed by the modifier, the toughening agent, the nucleating agent, and the antioxidant is usually the smallest. However, in some embodiments, it is also possible not to add the toughening agent, the nucleating agent, and the antioxidant to the composite current collector base film.

[0026] In some embodiments, 70wt%-80wt% of a polyolefin such as polypropylene, 5wt%-10wt% of a toughening agent, 0wt%-5wt% of a nucleating agent, 0wt%-1wt% of an antioxidant, and 10wt%-20wt% of a modifier can be melt-granulated to form a mixture, and then the mixture is melt-extruded through a co-extrusion molding process in a co-extrusion molding step, cooled and formed into a cast sheet, and then the cast sheet is stretched and heat-set to obtain a composite current collector base film.

[0027] Further, in this embodiment, the screw temperature of the granulator in the melt granulation step is 180°C-230°C, the melt temperature is 200°C-250°C, the pelletizing temperature is 250°C-300°C, and the pelletizing speed is 2000rpm-3000rpm. In some embodiments, the granulator parameters are screw temperature of 220°C, melt temperature of 210°C, pelletizing temperature of 270°C, and pelletizing speed of 2500rpm.

[0028] Furthermore, in the present embodiment, the melt extrusion temperature of the mixture in the co-extrusion molding step is 200°C-250°C, the rotation speed is 100-300 rpm, and it is cooled and formed into a cast sheet at 20°C-50°C, and then the cast sheet is longitudinally stretched at 110°C-160°C and a stretching ratio of 4 times to 7 times, and transversely stretched at 140°C-180°C and a stretching ratio of 3 times to 6 times, and finally the cast sheet is heat-set at 130°C-160°C to obtain the composite current collector base film used.

[0029] See also Figure 3 In some embodiments, the preparation method of the modifier includes the following steps: a step of forming a zirconium oxychloride aqueous solution: first, weighing 50 mg-100 mg of zirconium oxychloride octahydrate and adding it to 30 ml-50 ml of pure water for ultrasonic dispersion to obtain a zirconium oxychloride aqueous solution; a step of adding and stirring: then weighing 20 mg-50 mg of graphene oxide (GO) and adding it to the above zirconium oxychloride aqueous solution, and stirring it for 2h-5h; a step of adjusting the pH value: adding a certain amount of pH adjuster to adjust the pH value of the zirconium oxychloride aqueous solution to 10-11 to obtain a mixed solution; and a high-temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor and reacting it at a high temperature of 150°C-200°C for 12h-24h; taking out the mixed solution, washing it with anhydrous ethanol, filtering it, and drying it to obtain the modifier, which is a graphene oxide-nano zirconium oxide composite material.

[0030] See also Figure 4In some embodiments, the preparation method of the modifier includes the following steps: an intermediate solution forming step: first weighing 50 mg-100 mg of tetrabutyl titanate and adding it to a mixed solution formed by 30 ml-50 ml of deionized water and tetrabutylammonium hydroxide to obtain an intermediate solution; adding stirring step: weighing 20 mg-50 mg of graphene oxide and adding it to the intermediate solution, and stirring it for 2h-5h; pH value adjustment step: adding a certain amount of pH value adjuster to adjust the pH value of the intermediate solution to 10-11 to obtain a mixed solution; and a high temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor, reacting at a high temperature of 150°C-200°C for 12h-24h, then taking out the mixed solution, washing, filtering, and drying to obtain a graphene oxide-nano titanium oxide composite material.

[0031] In this embodiment, the pH adjuster is potassium hydroxide (KOH), but it is not limited thereto. In some embodiments, the pH adjuster may also be one or more of ammonia water (NH4OH), sodium hydroxide (NaOH), sodium dihydrogen phosphate (NaH2PO4), and potassium dihydrogen phosphate (KH2PO4).

[0032] In the invention, some parameters are designed to conduct experiments, and the experimental process and results are summarized as follows.

[0033] Example 1

[0034] 80wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 10wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 150°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated to form a mixture, and then the mixture is melt-extruded at an extrusion temperature of 200°C-250°C and a rotation speed of 100 rpm- The film was heated to 300 rpm and then cooled at 20°C-50°C to be formed into a cast sheet. The cast sheet was then longitudinally stretched at 110°C-160°C and a stretching ratio of 4-7 times. The cast sheet was transversely stretched at 140°C-180°C and a stretching ratio of 3-6 times. Finally, the cast sheet was heat-set at 130°C-160°C to obtain the composite current collector base film used, and the conductivity, surface tension, stretching and needle punching and other physical properties were tested.

[0035] Example 2

[0036] 80wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 10wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 180°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated, and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0037] Example 3

[0038] 80wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 10wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 180°C and the reaction time is 24h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated, and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0039] Example 4

[0040] 80wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 10wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 200°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0041] Example 5

[0042] 75wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 15wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 180°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0043] Example 6

[0044] 70wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 20wt% of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 180°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated, and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0045] Example 7

[0046] 80wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 10wt% of graphene oxide (GO)-nano-titanium dioxide (TiO2) metal oxide composite material (wherein the hydrothermal synthesis temperature is 180°C and the reaction time is 12h), 1wt% of ZnAA, and 0.1wt% of BHT264 are melt-granulated, and the extrusion and stretching conditions are the same as in Example 1 to obtain the composite current collector base film used, and the physical properties data such as conductivity, surface tension, and stretching and needle punching are tested.

[0047] Comparative Example 1

[0048] 90wt% of polypropylene, 8.9wt% of polymethyl methacrylate, 1wt% of ZnAA, and 0.1wt% of BHT264 were melt-granulated, and the extrusion and stretching conditions were the same as in Example 1 to obtain the composite current collector base film used, and the conductivity, surface tension, stretching and needle punching and other physical properties were tested.

[0049] Comparative Example 2

[0050] 80wt% polypropylene, 8.9wt% polymethyl methacrylate, 10wt% nano ZrO2, 1wt% ZnAA, and 0.1wt% BHT264 were melt-granulated and extruded and stretched under the same conditions as in Example 1 to obtain the composite current collector base film. The conductivity, surface tension, stretching and needle punching properties were tested.

[0051] Surface tension test method:

[0052] Use a surface tension test pen (dyne pen) to test directly. The specific method is as follows: select an intermediate value such as 38mN / m as the starting point during the test. If the test pen wets the surface of the substrate within 2 seconds, the surface tension of the substrate is greater than or just the selected value. You need to select a larger test pen for testing until the test result shrinks into a water droplet (spherical) within 2 seconds. The value before this test is regarded as the surface energy of the substrate.

[0053] Tensile test method: GB / T 1040.3-2006

[0054] The sample was cut into strips with a width of 15 mm using a cutting machine. During stretching, the stretching interval was set to 10 cm and the speed was set to 100 mm / min to obtain the corresponding stretching data.

[0055] Puncture test method: GB / T 36363-2018

[0056] The film was flattened and clamped in a fixture, and punctured at a speed of 100 mm / min to obtain corresponding puncture data.

[0057] The above experimental results are summarized as shown in Table 1. From the comparison between the embodiments and the comparative examples, it can be found that the surface tension of embodiment 6 is the largest, the surface tension of embodiment 5 is the second, and the surface tension values ​​of embodiments 2 and 7 are lower, indicating that: 1) the greater the amount of metal added, the greater the surface roughness of the base film; 2) different metal oxides have similar effects on the surface roughness of the film; 3) the performance of the graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material with hydrothermal conditions of 180°C and reaction time of 12h is the best. The reason may be that the nanoparticles will agglomerate if the reaction time is too long, and the temperature is too high or too low, which will lead to incomplete reaction or agglomeration of the nanoparticles.

[0058] Table 1: Surface tension values ​​in Examples and Comparative Examples

[0059]

[0060]

[0061] The above experimental results are summarized as follows Figure 5 As shown, from Figure 5 The results show that the ionic conductivity data show that the introduction of graphene oxide (GO) can significantly improve the conductivity of the base film, and the ionic conductivity of Example 5 is slightly higher than that of Example 6. This is because the conductivity of metal oxides is not very good, and excessive addition will lead to a decrease in conductivity.

[0062] The above experimental results are summarized as shown in Table 2. From the mechanical properties data, it can be seen that the introduction of nano metal oxides can significantly improve the tensile and needle puncture properties of the base film. When the amount of metal oxides continues to increase, the improvement of the mechanical properties of the base film is not obvious. Based on Table 1 and Table 2 and Figure 5 It can be concluded that when the addition amount of graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material is 15%, the hydrothermal reaction conditions are 180°C and the reaction time is 12h, the performance of the base film is the best.

[0063] Table 2: Mechanical properties test data of base film in examples and comparative examples

[0064]

[0065] In summary, in order to improve the problem of insufficient mechanical properties of the current composite current collector base film, as well as other problems such as surface roughness and conductivity, the present invention proposes a method of synthesizing graphene oxide (GO)-nano zirconium dioxide (ZrO2) metal oxide composite material by hydrothermal method, and introducing the material into the base film by virtue of the advantages of high specific surface area, large mechanical properties and good conductivity of the composite material, so as to improve the overall mechanical and electrical properties of the base film. Therefore, the present invention introduces graphene oxide-nano metal oxide composite in the base film production process, and improves the mechanical properties and surface roughness of the base film by virtue of the advantages of small particle size, large specific surface area and good mechanical properties of nanomaterials, which not only reduces the perforation phenomenon of the base film during the sputtering process, but also improves the bonding force between the base film and the metal to a certain extent; and at the same time, introducing a certain amount of graphene oxide can effectively improve the conductivity of the base film, and by virtue of the good conductivity of graphene, the conductivity of the composite current collector can be improved to a certain extent, so that the problems of insufficient mechanical properties, surface roughness, conductivity and other properties of the current composite current collector base film can be effectively solved.

[0066] The phrase "in some embodiments" and "in various embodiments" is used repeatedly. The phrase generally does not refer to the same embodiment; however, it may refer to the same embodiment. The words "including," "having," and "comprising" are synonymous unless the context indicates otherwise.

[0067] The above description is only an embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application has been disclosed as above with specific embodiments, it is not intended to limit the present application. Any technician familiar with the profession can make slight changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present application. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A method for preparing a composite current collector base film, characterized in that: The following steps are involved: Melt granulation step: melt granulating the polyolefin and the modifier to form a mixed material; as well as Co-extrusion step: melt-extrude the mixed material, cool and shape it to form a cast sheet, and then stretch and heat-shape the cast sheet to obtain the composite current collector base film; Wherein, the preparation method of the modifier comprises the following steps: Steps for forming a zirconium oxychloride aqueous solution: adding zirconium oxychloride octahydrate into pure water for ultrasonic dispersion to obtain a zirconium oxychloride aqueous solution; Adding and stirring step: adding graphene oxide to the zirconium oxychloride aqueous solution and stirring; pH adjustment step: adding a certain amount of pH adjuster to adjust the pH value of the zirconium oxychloride aqueous solution to 10-11 to obtain a mixed solution; and High temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor, reacting at a high temperature of 150°C-200°C for 12h-24h, then taking out the mixed solution, washing, filtering, and drying to obtain a graphene oxide-nano ZrO2 composite material.

2. A method for preparing a composite current collector base film, characterized in that: The following steps are involved: Melt granulation step: melt granulating the polyolefin and the modifier to form a mixed material; as well as Co-extrusion step: melt-extrude the mixed material, cool and shape it to form a cast sheet, and then stretch and heat-shape the cast sheet to obtain the composite current collector base film; Wherein, the preparation method of the modifier comprises the following steps: The intermediate solution forming step is: adding tetrabutyl titanate to a mixed solution formed by deionized water and tetrabutylammonium hydroxide to prepare an intermediate solution; Adding and stirring step: adding graphene oxide to the intermediate solution and stirring; pH adjustment step: adding a certain amount of pH adjuster to adjust the pH value of the intermediate solution to 10-11 to obtain a mixed solution; and High temperature reaction step: pouring the mixed solution into a polytetrafluoroethylene reactor, reacting at a high temperature of 150°C-200°C for 12h-24h, then taking out the mixed solution, washing, filtering, and drying to obtain a graphene oxide-nano-TiO2 composite material.

3. The method for preparing a composite current collector substrate according to claim 1 or 2, characterized in that: In the melt granulation step, the screw temperature of the granulator is 180°C-230°C, the melt temperature is 200°C-250°C, the pelletizing temperature is 250°C-300°C, and the pelletizing speed is 2000rpm-3000rpm.

4. The method for preparing a composite current collector substrate according to claim 1 or 2, characterized in that: The pH value adjuster includes one or more of potassium hydroxide, ammonia water, sodium hydroxide, sodium dihydrogen phosphate, and potassium dihydrogen phosphate.

Citation Information

Patent Citations

  • Nanoparticle / graphene oxide composite modified high polymer material and preparation thereof

    CN107880484A

  • Ultrathin and low-resistance conductive polymer film and preparation method thereof

    CN117343429A